THE PROMISSORY NOTE FROM THE PERSPECTIVE OF BRAZILIAN BUSINESS LAW (CIPEEX, 2025)
This paper analyzes promissory notes from the perspective of Brazilian Business Law, highlighting their legal nature, essential elements, and relevance in commercial relations. This is a bibliographical study based on the Uniform Geneva Law, incorporated into the Brazilian legal system by Decree No. 57.663/1966, as well as specialized doctrine and jurisprudence. A promissory note is a credit instrument that contains a pure and simple promise to pay a specified amount, within a previously defined timeframe and location. Its main distinguishing feature lies in its autonomy and enforceability, allowing the creditor to quickly collect the amount due through legal means in the event of default. In the corporate sphere, promissory notes play a strategic role, as they guarantee security for commercial transactions, enabling installment payments, and fostering the flow of credit. The research shows that the promissory note presents essential requirements for its validity, such as the name “promissory note” inserted in the text itself, the unconditional promise of payment, the name of the beneficiary, the date and place of issuance, the amount to be paid and the signature of the issuer. Furthermore, the possibility of endorsement expands its usefulness, allowing its transfer to third parties and strengthening its role as a guarantee and wealth circulation instrument. The results indicate that, despite technological advancements and the emergence of new payment methods, promissory notes continue to be widely used in the Brazilian market, especially in sectors that depend on credit and mutual trust between parties. Their simplicity, effectiveness, and legal support make them an efficient mechanism for concluding deals and reducing risks in business relationships. The conclusion is that promissory notes, by combining characteristics such as formality, autonomy, transferability, and enforceability, play a fundamental role in the dynamics of business activities, contributing to the stability of commercial relations and strengthening credit in the country.